Mengukur hubungan minat kerjaya dengan jantina dan aliran dalam kalangan pelajar tingkatan empat di tiga buah Sekolah Menengah daerah Johor Bahru - Haron, Sabariah (2013)
This descriptive research aims to identify the relationship between job interests with demography factors among form 4 students of secondary school in Johore Bahru. A total of 400 students form 4 from three secondary schools in Johore Bahru were involved. Researcher has used Sidek’s Vocational Preference Inventory (VPI) to identify the job interest among the students. The finding of the pilot study indicated that the instrument’s coefficient alpha is 0.915. The data from the survey were analysed using the Statistical Package of Social Sciences (SPSS) version 20.0, involving descriptive and inferential statistics of t test, ANOVA and Chi-Square. Findings of the study show that majority of the students were interested with investigative job, followed by Enterprising. Job interest that has the lowest frequency is Social. ANOVA analysis by courses show Social and Enterprising are not significant with gender but another job interest are significant. T-test and Chi-Square show that there are no differences and relationship between job interest and gender. Finally, the study proposed several suggestions for the attention and future research